An Equivalent 3D Otsu’s Thresholding Method - Sthitpattanapongsa, Puthipong; Srinark, Thitiwan (Advances in Image and Video Technology, 2011)
Due to unsatisfactory segmentation results when images contain noise by the Otsu’s thresholding method. Two-dimensional (2D) and three-dimensional (3D) Otsu’s methods thus were proposed. These methods utilize not only grey levels of pixels but also their spatial informations such as mean and median values. The 3D Otsu’s methods use both kinds of spatial information while 2D Otsu’s methods use only one. Consequently the 3D Otsu’s methods more resist to noise, but also require more computational time than the 2D ones. We thus propose a method to reduce computational time and still provide satisfactory results. Unlike the 3D Otsu’s methods, our method selects each threshold component in the threshold vector independently instead of one threshold vector. The experimental results show that our method is more robust against noise, and its computational time is very close to that of the 2D Otsu’s methods.